The Neotropical mite genus Neopilizetes (Oribatida: Galumnidae): redescription of N. neotropicus, rediagnosis of the genus, and descriptions of four new species - Amorim, Saulo S.; Norton, Roy A.; Oliveira, Anibal R. (Zootaxa, 2018)
Neopilizetes is a genus of the oribatid mite family Galumnidae that was first characterized by having well-developed setae, a dorsosejugal suture, and raised striae on the prodorsum and notogaster. It was proposed to accommodate Pilizetes neotropicus Balogh & Mahunka 1978 from Brazil—the only supposed Pilizetes species known outside the Ethiopian Region—and it has remained monotypic. We found adults of N. neotropicus and four related species in soil–litter interface samples of a single cacao plantation in Ilhéus, Bahia, Brazil. Herein we: redescribe N. neotropicus; describe Neopilizetes thoracicus n. sp., Neopilizetes tigris n. sp., Neopilizetes triumnasus n. sp. and Neopilizetes unumnasus n. sp., and use this information to develop a new concept and expanded diagnosis of Neopilizetes. A key to the five species is provided, and we offer reasons for rejecting the classification of Neopilizetes as a subgenus of Pilizetes.